Measuring The Economic Contribution of Tourism: An Improvement in Indonesia - Akhmad Mun'im (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
The implementation of the international standard manual is an effort made by every national statistical office (NSO) in developing its official statistics so that they have comparability at the global level. The methods recommended in the international standard manual have also been refined and adapted to other standard manuals so that the resulting official statistics are consistent with each other. Statistics Indonesia (BPS) as the Indonesian NSO adopts various international standard manuals, including the International Recommendations for Tourism Statistics (IRTS) and Tourism Satellite Accounts: Recommended Methodological Framework (TSA:RMF) 2008 manuals recommended by UNWTO in calculating the tourism contribution in the Indonesian economy. Both recommend the utilization of the supply and use table (SUT) framework that explains tourism supply-demand in measuring tourism contributions. This approach is an improvement from the previous approach which used shock analysis under input-output (I-O) framework in calculating tourism contributions. Through the supply-demand of tourism sector approach, the amount of tourism direct gross domestic product (TDGDP) is obtained which shows the contribution of tourism to the national economy. During 2016-2019, the tourism sector contributed around 4.6 – 4.9 percent to the Indonesian economy.